ANALISIS BAURAN PEMASARAN PADA PRODUK DAGING AYAM: (Studi Kasus: Konsumen Ayam Ras Mulyo Pitik Di Kabupaten Bekasi) - Lutfiadi, Ridwan; Ismarani; Tokan, Antika Rizky (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
Mulyo Pitik is one of the businesses engaged in the sale of broiler. Mulyo Pitik’s marketing areas are Cibitung Subdistrict, South Tambun Subdistrict and its surroundings. This study aims to determine: (1) general characteristics of consumers at Mulyo Pitik; (2) Do marketing mix factors affect simultaneously and partially the buying decision of broiler Mulyo Pitik in Bekasi District. This study uses a survey method and the analytical tools used are Descriptive Analysis and Multiple Linear Regression Analysis using the SPSS 24 application. The results of the data analysis show that there are two factors that influence purchasing decisions significantly, namely the product factor because chicken is a food ingredient that is often consumed by consumers in their daily life and the factor that influences subsequent decisions is the price factor because consumers are more dominant in women and as it is known that women are more sensitive consider price in purchasing decisions